Wykorzystanie analitycznego procesu hierarchicznego w analizie SWOT jednostek administracyjnych - Łuczak, Aleksandra; Wysocki, Feliks (The Application of the Analytic Hierarchy Process in SWOT Analysis of Administrative Districts, 2009)
In this paper, we present a quantified SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) with the use of Saaty's method of analytic hierarchy process (the AHP). This method is useful in development planning. Its essence, concepts and rules of implementation have been presented in details. This approach is a complex procedure, which appears to be useful in making decisions concerning development of administrative districts. The AHP method has been used for the first time to work out SWOT analysis of administrative districts. This problem was illustrated with the use of SWOT analysis of administrative districts in province of Wielkopolska. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 47, s. 113-122